Radish (Raphanus Sativus): Potential antioxidant role of bioactive compounds extracted from radish leaves - A review - Rozina Shahadat Khan, Sunair Siddique Khan, Romaisa Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Radish (Raphanus Sativus) used against many toxicants as a natural drug, is a worldwide grown cruciferous root crop with root part the main edible organ and leave part, which in dried form are effective as functional foods. Radish (Raphanus Sativus) that exhibits variety of colors has rich content of vitamins, phenolic compounds, dietary fiber and Phyto-anthocyanin. Based on physico-chemical, nutritional, antioxidant and microbiological properties radish leaves are more nutritionally rich than roots. Leaves are premier source of phenol, flavonoid and have free radical hunting ability. The antioxidant biomarker compound Rutin has been identified only in radish leaves. Therefore the inclusion of Radish leaves in the human diet could have higher bioactive compounds especially flavonoid availability than roots. Conclusion: Consumption of radish leaves mostly discarded may present nutritional and medicinal value to human health especially due to their Antioxidant Activity. Moreover to develop novel functional products more exploration is required to approximate other bioactive compounds from the radish leaves. Keywords: Radish (Raphanus Sativus), bioactive compounds Antioxidants and Skin